The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ma13163464
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Strengthening Model of Cu–Fe In-Situ Composites

Abstract: The tensile strength evolution and strengthening mechanism of Cu–Fe in-situ composites were investigated using both experiments and theoretical analysis. Experimentally, the tensile strength evolution of the in-situ composites with a cold deformation strain was studied using the model alloys Cu–11Fe, Cu–14Fe, and Cu–17Fe, and the effect of the strain on the matrix of the in-situ composites was studied using the model alloys Cu–3Fe and Cu–4.3Fe. The tensile strength was related to the microstructure and to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…2(a). The primary iron dendrites were embedded in the copper matrix with random orientation, which was similar to the previous research results ( Ref 6,7,9). Hot rolling and cold drawing to g = 3 transformed the primary iron dendrites with random orientation into iron fibers and tadpole shaped iron grains parallel to the deformation direction, as shown in Fig.…”
Section: Evolution Of Microstructuresupporting
confidence: 89%
“…2(a). The primary iron dendrites were embedded in the copper matrix with random orientation, which was similar to the previous research results ( Ref 6,7,9). Hot rolling and cold drawing to g = 3 transformed the primary iron dendrites with random orientation into iron fibers and tadpole shaped iron grains parallel to the deformation direction, as shown in Fig.…”
Section: Evolution Of Microstructuresupporting
confidence: 89%
“…Copper matrix composites have a wide range of applications comprising high electrical and thermal conductivities. Cu-Al 2 O 3 composites are mostly used in electrode materials, especially spot welding [24,[29][30][31][32][33]. These composites are ordinarily prepared by conventional powder metallurgy [34] or casting [35] routes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, copper matrix composites got a great interest and are developed for many applications like heat exchangers, sensitive electrical circuits, brushes, springs, bearings, and bushing [5][6][7][8]. Among copper matrix composites, Cu-Fe composites got the attention of many researchers because of their low cost, compared with other metals beside their good mechanical properties [9][10][11][12][13][14][15][16]. Jerman, G.A.…”
Section: Introductionmentioning
confidence: 99%
“…They found that corrosion resistance was increased by 75%, wear resistance was increased by 30%. Keming Liu et al [22] studied the effect of Fe content and drawing strain on tensile strength of Cu-Fe composite produced by casting. They found that tensile strength increased with increasing both Fe content and drawing strain.…”
Section: Introductionmentioning
confidence: 99%